Work Environment as the Primary Determinant of Teacher Performance: A Quantitative Study of Job Demands and Organizational Resources in Indonesian Secondary Education - Septa Puteri Puspitasari; Meilia Rosani; Nuril Furkan (Yayasan Sembilan Pemuda Indonesia, 2026)
Teacher performance is fundamental to school quality, yet the relative influence of job demands versus organizational resources remains underexplored in Indonesian secondary education. This study examines the effects of workload and work environment on teacher performance at SMA Negeri 1 Sungai Lilin, Indonesia. Using a descriptive quantitative survey design, data were collected from 50 teachers via a five-point Likert-scale questionnaire and analyzed through multiple linear regression using SPSS 25. Simple regression analyses revealed that workload negatively affects performance (B = -0.236, p = 0.016, R² = 0.116), while work environment positively affects performance (B = 0.616, p < 0.001, R² = 0.451). However, in the multiple regression model, workload became non-significant (B = -0.099, p = 0.207), whereas work environment remained a strong predictor (B = 0.575, p < 0.001). The simultaneous model explains 46.9% of performance variance (F = 20.795, p < 0.001). These findings demonstrate that the work environment is the dominant organizational factor explaining teacher performance when tested alongside workload. The study contributes to educational management literature by clarifying the relative roles of job demands and organizational resources, suggesting that school improvement efforts should prioritize strengthening physical and psychosocial work conditions alongside workload management.